Implementation of Prudential Principles in Risk Management in Digital Banking Business Models - Redita Suryadarma, Fatika; Pujiyono, Pujiyono (Devotion : Journal of Research and Community Service, 2025)
In the era of digital transformation, banking faces various challenges such as cyber, operational, and reputation risks, so that the principle of prudence in risk management of banking business models becomes an urgency that cannot be ignored. The purpose of this study is to analyze the implementation of the principle of prudence in risk management in digital banking business models. This study uses a normative research method with a legislative approach and a conceptual approach. The results of this study indicate that the principle of prudence in the digital banking sector plays a fundamental role in maintaining the stability and integrity of financial institutions. This principle not only helps in risk management, but also ensures a strong relationship between banks and customers, which is based on trust.